2018
DOI: 10.1016/j.geb.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The stable fixtures problem with payments

Abstract: We generalize two well-known game-theoretic models by introducing multiple partners matching games, defined by a graph G = (N, E), with an integer vertex capacity function b and an edge weighting w. The set N consists of a number of players that are to form a set M ⊆ E of 2-player coalitions ij with value w(ij), such that each player i is in at most b(i) coalitions. A payoff vector is a mapping p :can form, possibly only after withdrawing from one of their existing 2-player coalitions, a new 2-player coalition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Open Questions Matching Games generalize naturally to b-matching games, where instead the underlying optimization problem is to find an edge subset M with |M ∩δ(v)| ≤ b v for each node v. Biro, Kern, Paulusma, and Wojuteczky [4] showed that the core-separation problem when b v > 2 for some vertex v, is coNP-Hard. Despite this, the complexity of computing the nucleolus of these games is open.…”
Section: Computing the Nucleolusmentioning
confidence: 99%
See 1 more Smart Citation
“…Open Questions Matching Games generalize naturally to b-matching games, where instead the underlying optimization problem is to find an edge subset M with |M ∩δ(v)| ≤ b v for each node v. Biro, Kern, Paulusma, and Wojuteczky [4] showed that the core-separation problem when b v > 2 for some vertex v, is coNP-Hard. Despite this, the complexity of computing the nucleolus of these games is open.…”
Section: Computing the Nucleolusmentioning
confidence: 99%
“…Kern and Paulusma state the question of computing the nucleolus for general matching games as an important open problem in 2003 [30]. In 2008, Deng and Fang [10] conjectured this problem to be NP-hard, and in 2017 Biró, Kern, Paulusma, and Wojuteczky [4] reaffirmed this problem as an interesting open question. Theorem 1 settles the question, providing a polynomial-time algorithm to compute the nucleolus of a general instance of a weighted cooperative matching game.…”
Section: Introductionmentioning
confidence: 99%
“…Note that 1-assignment games correspond to assignment games. A b-matching game is called a multiple partners matching game in the paper of Biró et al (2018).…”
Section: Matching Games and Generalizationsmentioning
confidence: 99%
“…The goal is to decide if (G, b, w) has a (pairwise) stable solution, that is, a solution with no blocking pairs. This problem is called the Stable Fixtures with Payments (SFP) problem (Biró et al, 2018). Restrictions of SFP are called: (Sotomayor, 1992);…”
Section: If Ij /mentioning
confidence: 99%
“…PPAD-hardness [31] is considered a somewhat weaker evidence of intractability than NP-hardness that applies for problems whose decision versions have a 'yes' answer for sure. Note that smf is one of the very few problems in stability [3] where a stable solution exists, but no extension of the Gale-Shapley algorithm is known to solve it -not even a variant with exponential running time.…”
Section: Problem 2 Smfmentioning
confidence: 99%